Uslūb al-Kināyah fī al-Qur’ān al-Karīm wa al-Istifādah minhu fī Tanmiyyah al-Qiyām al-Akhlāqiyyah ladai al-Ṭālibāt bi al-Jāmi’ah - Sapitri, Nur; Qosim, Muhammad Nanang (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to reveal the method of metonymy included in Surat An-Nisa so that the researcher noticed that one of the holy Qur’an’s surah, Surah An-Nisa, is full of the provisions of Sharia law. It organizes the internal and external lives of Muslims, and talks about important matters related to women, the home, and the family, but most of the provisions discuss women’s issues and then explain the husband‘s rights over her husband and vice versa. Also, from the standpoint of rhetoric, this surah is full of the style of metonymy, which should be left out of the politeness of human feelings and moral matters, as most of what this surah explained are the matters of the family and women. The researcher wanted to identify the style of metonymy in Surat An-Nisa and its benefit in developing moral values among female students at the university. The method of completion of this research was on the analytical descriptive approach, the way for the researcher to analyze the method of the metaphor in Surah an-Nisa with the extraction of the hidden meaning of the rhetorical and ethical response to each method and the current research has proved that the method of the metaphor in surah an-Nisa of verse 1 to 107 contained fifty examples of the metaphor. This proved that the meanings of the verses showed the greatness of Allah’s power, the relation with justice, the relation with the characteristics of the ummah, and some words that we can’t mention, the metaphor contained in Surah an-Nisa verses 1 to 107 had its significant effect in the development of moral values ​​among students at the University of Ar-Raayah.